Transformations and transfer of Tantra in Asia and beyond - Keul, István (Religion and society (Hague, Netherlands) ;, 2012)
The essays in this volume, written by specialists working in the field of tantric studies, attempt to trace processes of transformation and transfer that occurred in the history of tantra from around the seventh century and up to the present. The volume gathers contributions on South Asia, Tibet, China, Mongolia, Japan, North America, and Western Europe. The chapters cover a wide thematic area, which includes modern Bengali tantric practitioners, tantric ritual in medieval China, the South Asian cults of the mother goddesses, the way of Buddhism into Mongolia, and countercultural echoes of con.